Influence of Selenium Supplementation on Oxidative Stress and Inflammatory Response in High Intensity Exercise - Irawan, Roy; Wahyudi , Heri; Bawono, Mokhamad; Roepajadi, Joesoef; Rimawati, Nanda; Wijayanto, Adi (Jurnal Kesehatan Masyarakat, 2025)
Exhaustive exercise could increase oxygen consumption 10 to 20 times folds which can then increase oxidative stress which is characterized by an increase in Reactive Oxygen Species (ROS). Increased oxidative stress (ROS) during exercise could cause cell damage. Selenium is a trace element that is believed to have antioxidant and anti-inflammatory activity. Objectives: This study aimed to determine the effectiveness of a 28-day supplementation period on plasma MDA and HMGB1 levels after high-intensity exercise activities. Methods: This study was experimental, with a pretest-posttest control group design approach. A total of 28 Sports Science Department students at Universitas Negeri Surabaya who met the inclusion and exclusion criteria participated in the study. Through simple random sampling, participation was divided into 2 groups, namely the selenium group (SG) and the placebo (PL) group. Selenium supplements for SG were 200 mcg/day, and PL was 100mg corn starch capsules, both groups consumed in 28 days. Participants performed bench-stepping by Newham with 10 sets x 10 repetitions, with 1-minute intervals. Plasma MDA and HMGB1 measurements were carried out immediately after, 24 hours after, and 48 hours after bench-stepping. Data on changes in plasma levels of MDA and HMGB1 were tested using repeated measures ANOVA with a significance level of P<0.05. Result: there was a significant difference in the plasma MDA and HMGB1 between each group with the significance value of MDA that was p = 0.000 and the significance value of HMGB1 that was p = 0.000. Selenium supplementation for 28 days reduces the increase in oxidative stress (MDA) and increase in HMGB1 after high-intensity exercise activities.